Capsaicin suppresses ciliary function, while inducing permeability in bronchial epithelial cell cultures of COPD patients - Toy, Halil Ibrahim; Yildiz, Abdullah Burak; Tasdemir Kahraman, Demet; Ilhan, Sedat; Dikensoy, Oner; Bayram, Hasan (Frontiers in Pharmacology, 2022)
Tear gas is widely used to halt mass demonstrations. Studies have reported its adverse effects on multiple organ systems; however, its effect on individuals with chronic respiratory diseases and the underlying mechanisms of these effects are unclear. For the first time in the literature, we investigated the effects of capsaicin, the active ingredient of tear gas, on bronchial epithelial cell (BEC) cultures obtained from well-characterized groups of nonsmokers, smokers, and patients with chronic obstructive pulmonary disease (COPD). BEC cultures were incubated with 50-500 μM capsaicin in the absence and presence of formoterol (1μM) and roflumilast (0.1μM) for 24 hours. Ciliary beat frequency (CBF) and transepithelial electrical resistance (TEER) were assessed at T1/4, T1/2, T1, T2, T4, T6, and T24 h, whereas the release of granulocyte-macrophage colony-stimulating factor (GM-CSF), interleukin (IL)-8, and lactate dehydrogenase (LDH) was measured at T24 h. Capsaicin (250µM) significantly decreased CBF of all BEC cultures from T1/4 h to T24 h (p<0.05). Formoterol significantly prevented decreases in CBF induced by capsaicin. Higher concentrations of capsaicin (250-500 μM) significantly reduced TEER of BECs from nonsmokers (T2-T24 h), smokers (T24 h) and COPD patients (T2 and T24 h), which was partially prevented by roflumilast. Capsaicin (500μM) decreased release of IL-8 (p<0.0001) and GM-CSF (p<0.05) while inducing release of LDH in BECs (p<0.05), and this was more prominent in BEC from patients with COPD. In conclusion, our findings demonstrate that capsaicin can suppress ciliary activity and cytokine release from BECs, induce BEC culture permeability and cellular toxicity and that these effects can be partially prevented by formoterol and roflumilast.